Incidence and etiology of traumatic spinal cord injury in Rwanda: a prospective population-based study - Kanyoni, Maurice; Wikmar, Lena Nilsson; Philips, Joliana; Joseph, Conran; Tumusiime, David K. (Frontiers in Neurology, 2024)
Background Traumatic spinal cord injury (TSCI) is not only a life-threatening but also life changing event that happens suddenly, the effects extends beyond the TSCI survivors to include their families. In Rwanda to the best knowledge of authors, there is no published information on the epidemiology of TSCI. The aim of this study was therefore to determine the incidence rate, etiology and injury characteristics of TSCI. Methods All survivors of acute TSCI who met the inclusion criteria were prospectively recruited for a one-year period. The International Spinal Cord Injury Core Data Set was used to collect the minimum set of variables to facilitate worldwide comparison of epidemiological data, while the International Standards for the Neurological Classification was used to categorize TSCI according to the American Spinal Injury Association Impairment Scale (AIS). Data were collected by trained physiotherapists. Study design A prospective, open-ended, cohort study design. Setting All referral hospitals within the Republic of Rwanda. Results Overall, 122 adult individuals sustained a TSCI between 10th October 2019 until 9th October 2020 and all consented to take part in the study. The male-to-female ratio was 3.9:1, and the mean age was 42.5 (SD = ±14.8) years. The crude incidence rate of TSCI was 22.2 per million people (95% CI, 18.4–26.5) with significant differences in sex-adjusted rates for all age groups while men 46 years of age and older presented with the highest incidence. The leading causes of TSCI were falls (73.8%), followed by road traffic accidents (18.9%). Moreover, SCI lesions of the cervical region (n = 69) were the most common, followed by the lumbosacral region (n = 27). Fifty-one (41.8%) participants were diagnosed as complete injury, i.e., AIS A, while incomplete injury category C constituted 35 (28.7%). Conclusion The incidence and etiology of TSCI in Rwanda are comparable to worldwide estimates and figures. Largely, the etiology of TSCI are preventable as it is caused due to falls and road traffic accidents. There is a need to consider preventive strategies and policies on activities that predispose people to falls. Policies should focus largely on occupational health and safety in both formal and informal sectors of work.